Moorea producens gen. nov., sp. nov. and Moorea bouillonii comb. nov., tropical marine cyanobacteria rich in bioactive secondary metabolites - Engene, Niclas; Rottacker, Erin C; Kaštovský, Jan; Byrum, Tara; Choi, Hyukjae; Ellisman, Mark H; Komárek, Jiří; Gerwick, William H (International journal of systematic and evolutionary microbiology, 2012)
The filamentous cyanobacterial genus Moorea gen. nov., described here under the provisions of the International Code of Botanical Nomenclature, is a cosmopolitan pan-tropical group abundant in the marine benthos. Members of the genus Moorea are photosynthetic (containing phycocyanin, phycoerythrin, allophycocyanin and chlorophyll a), but non-diazotrophic (lack heterocysts and nitrogenase reductase genes). The cells (discoid and 25-80 µm wide) are arranged in long filaments (<10 cm in length) and often form extensive mats or blooms in shallow water. The cells are surrounded by thick polysaccharide sheaths covered by a rich diversity of heterotrophic micro-organisms. A distinctive character of this genus is its extraordinarily rich production of bioactive secondary metabolites. This is matched by genomes rich in polyketide synthase and non-ribosomal peptide synthetase biosynthetic genes which are dedicated to secondary metabolism. The encoded natural products are sometimes responsible for harmful algae blooms and, due to morphological resemblance to the genus Lyngbya, this group has often been incorrectly cited in the literature. We here describe two species of the genus Moorea: Moorea producens sp. nov. (type species of the genus) with 3L(T) as the nomenclature type, and Moorea bouillonii comb. nov. with PNG5-198(R) as the nomenclature type.
Keywords: Photosynthesis; Biosynthetic Pathways; DNA bakterií; DNA, Ribosomal; Phylogeny; mikroskopie; Polyketide Synthases; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; polyketidsynthasy; RNA ribozomální 16S; Cluster Analysis; biologické pigmenty; RNA, Ribosomal, 16S; sinice; sekvenční analýza DNA; Pigments, Biological; biosyntetické dráhy; DNA, Bacterial; tropické klima; peptidsynthasy; Seawater; fylogeneze; shluková analýza; ribozomální DNA; Tropical Climate; biologické přípravky; Microscopy; Cyanobacteria; fotosyntéza; mořská voda; Peptide Synthases; Biological Products